Formulation du modèle MiSP coque tridimensionnel dégénéré - Ayad, Rezak; Batoz, Jean-Louis; Dhatt, Gouri (European Journal of Computational Mechanics, 2002)
This work deals with a mixed variational approach for the linear analysis of shells. MiSP model (Mixed Shear Projection) is based on the Hellinger-Reissner principle with a particular representation of the transverse shear strains. To improve the membrane behaviour of shells, a 3D representation of the “Fiber Rotation” concept is made and adapted to the formulation of the degenerated MiSP model. Two 4-node shell finite elements are developed: MiSP4-Q4 and MiSP4-FRQ. Several tests usually used to validate shell elements are presented. These show a quite good behaviour of these two elements.